IMPLIKATUR DALAM DISPLAY PICTURE BLACKBERRY MESSENGER TENTANG KENAIKAN HARGA BAHAN BAKAR MINYAK - Rini Afrilesa Jasmir (Universitas Muara Bungo, 2017)
This research is aimed at describing the implicature containing in blackberry messenger display picture about the rising of fuel price. The objectives of this writing are to explain the types of implicature containing in blackberry messenger display picture about the rising of fuel price, to analyze the meaning, and to identify its pragmatic functions.This thesis applied descriptive qualitative research in which the data are obtained from blackberry messenger display picture about the rising fuel price. The data are collected by observational method supported by note-taking and interviewing technique. Data analysis is conducted by referential identity method. The result of analysis is presented by formal and informal method.After analyzing the data, it is found that there are four types of implicature. They are (1) generalized conversational (31%) ; (2) particularized conversational ( 38%); (3) scalar (10%); and (4) conventional implicature (21%). The most commonly type found is particularized conversational implicature. This is due to the specific context in this implicature to make indirect speech. Besides, the users of blackberry messenger can also express their ideas is to quip and humor doing. The using of specific context to saved the threatening face of hearer. The meaning of implicature shows that the users of Blackberry Messenger disagree about the rising fuel prices (93%) because they knew the effect from the rising fuel prices is burden the people to fulfill their needs in the future. There three functions of implicature indicated. They are (1) assertive (41%), (2) directive (7%), and (3) expressive function (52%). Expressive function dominantly occurs in blackberry messenger display picture about the rising fuel prices.This is caused by the presentation of expressing feeling to quip. The function of the least discovered is directive function as speaker in this case does not directly provide influence through direct speech.Keywords :implicature, display picture, rising of fuel price